Genetic Analysis of African Swine Fever Virus From the 2018 Outbreak in South-Eastern Burundi - Hakizimana, Jean N.; Nyabongo, Lionel; Ntirandekura, Jean B.; Yona, Clara; Ntakirutimana, Désiré; Kamana, Olivier; Nauwynck, Hans; Misinzo, Gerald (Frontiers in Veterinary Science, 2020)
African swine fever (ASF) is a highly contagious viral disease which causes high mortality, approaching 100%, in domestic pigs and wild boars. The disease has neithero cure nor vaccine and it is caused by an ASF virus (ASFV), the only member of the family Asfarviridae, genus Asfivirus and the only known DNA arbovirus. Twenty four genotypes of ASFV have been described to date and all of them have been described in Africa. African swine fever is endemic in Burundi and several outbreaks have been reported in the country and continues to economically impact on small-scale farmers. This study aimed at genetic characterization of ASFV that caused an ASF outbreak in Rutana region, Burundi in the year 2018. Tissue samples from domestic pigs that died as a result of a severe hemorrhagic disease were collected in order to confirm the disease using polymerase chain reaction (PCR) and to conduct partial genome sequencing. Nucleotide sequences were obtained for the B646L (p72) gene, the intergenic fragment between I73R and I329L genes and the central variable region (CVR) of the B602L gene. Phylogenetic analysis of the Burundian 2018 ASFV grouped the virus within B646L (p72) genotype X and clustered together with those reported during the 1984 and 1990 outbreaks in Burundi with high nucleotide identity to some ASFV strains previously reported in neighboring East African countries, indicating a regional distribution of this ASFV genotype. Analysis of the intergenic fragment between I73R and I329L genes showed that the Burundian 2018 ASFV described in this study lacked a 32 base pair (bp) fragment present in the reference genotype X strain, Kenya 1950. In addition, the strain described in this study had the signature AAABNAABA at the CVR (B602L) gene, and showed 100% amino acid sequences identity to viruses responsible for recent ASF outbreaks in the region. The virus described in this study showed high genetic similarities with ASFV strains previously described in domestic pigs, wild suids and soft ticks in East African countries indicating a possible common wild source and continuous circulation in domestic pigs in the region.